Analisis Kebutuhan Pengembangan Media Pembelajaran Berbasis Mind Mapping Untuk Melatih Pemahaman Konsep Siswa Pada Pembelajaran Sejarah Di SMA - Anjelina, Fitria; Afriani, Rini (Jurnal Kronologi, 2025)
This research is motivated by the low ability of students to understand historical concepts and the lack of variety in the learning media used by teachers. The purpose of this study is to analyze the need for the development of a Mind Mapping-based learning medium in the material “Basic Concepts of History” to train students’ conceptual understanding skills. The development of learning media is considered essential to improve the quality of history learning, which is often perceived as less engaging and difficult for students to comprehend. The use of mind mapping learning media is expected to provide a solution by offering material that is more interactive, engaging, and easily accessible to students. This study employs a mixed-method approach (qualitative and quantitative) with data collection techniques including observation, interviews, and pretest questions. The results of the study indicate that teachers need varied and interactive learning media, students have access to personal devices to support the use of digital media, and schools provide adequate facilities. In conclusion, the researcher offers a solution through the development of Mind Mapping-based learning media, which is expected to enhance students’ conceptual understanding skills in history learning.